Method for producing zeolite molded article

The method of using a polymer crosslinking agent in the slurry for zeolite molded bodies addresses the issue of wear resistance during spray drying, resulting in zeolite molded bodies that are less prone to pulverization and flow issues.

JP2025053866APending Publication Date: 2025-04-07JGC CATALYSTS & CHEMICALS LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023162946
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-07

AI Technical Summary

Technical Problem

Existing methods for manufacturing zeolite molded bodies for use in suspended or fluidized beds face challenges in preventing wear and pulverization, particularly during the spray drying process.

Method used

A method involving the use of a slurry containing a zeolite, an inorganic binder, and a polymer crosslinking agent, which is then spray dried to form a zeolite molded body. The polymer crosslinking agent is used in a specific concentration range (0.01% to 10% by mass) to enhance the wear resistance of the molded body.

Benefits of technology

The method effectively produces zeolite molded bodies that are resistant to wear, even after calcination, by maintaining the binding between zeolite and inorganic binder through crosslinking, thus preventing pulverization and flow issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025053866000001
    Figure 2025053866000001
Patent Text Reader

Abstract

To provide a method for producing a zeolite molded article resistant to abrasion.SOLUTION: A method for producing a zeolite molded article comprises: a slurrying step of preparing slurry containing zeolite, an inorganic binder, and a polymer crosslinking agent; and a molding step of spray-drying the slurry to mold a zeolite molded article. A content of the polymer crosslinking agent contained in the slurry is in a range of 0.01 mass% to 10 mass% based on the total mass of the slurry excluding the polymer crosslinking agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a shaped body containing zeolite that is resistant to wear (highly wear-resistant). [Background technology]

[0002] Zeolite is a general term for crystalline porous aluminosilicates and crystalline metallosilicates. In addition, substances with a structure similar to that of zeolite are called zeolite-like substances. Zeolite and zeolite-like substances (hereinafter, zeolite and zeolite-like substances are collectively referred to as zeolite) have special pores derived from their crystal structure, and these pores are utilized for various applications. For example, zeolite is widely used for applications such as dehydrating agents and deodorants by utilizing the fact that compounds are adsorbed into the pores. In addition, zeolite is also used in gas separation membranes by utilizing the pore structure as a molecular sieve. Furthermore, zeolite is used in various catalytic reactions by utilizing the solid acidity and the molecular sieve function that it has.

[0003] Zeolites are used after being molded into a shape suitable for the application. For example, when used in a fixed bed as an adsorbent or catalyst, they may be molded into a cylindrical shape by extrusion molding, tablet molding, or the like. When used in a suspension bed or fluidized bed, they may be molded into a spherical shape by a spray drying method or the like. In particular, when used in a suspension bed or fluidized bed, there is a problem that the molded body is prone to wear because it flows. Various studies have been conducted so far with the aim of suppressing the powdering of spherically molded zeolites.

[0004] For example, Patent Document 1 discloses that a fluid catalytic cracking catalyst having a large pore volume and high wear resistance can be obtained by spray-drying an inorganic oxide matrix precursor containing basic aluminum chloride to obtain a catalyst composition, and then supporting sulfuric acid or a sulfate on the catalyst composition. Patent Document 2 discloses that a catalyst having high accessibility and high wear resistance can be obtained by a method for producing a catalyst comprising the steps of: a) producing a slurry containing clay, zeolite, and quasicrystalline boehmite (provided that the slurry does not contain peptized quasicrystalline boehmite); b) adding a monovalent acid to the slurry; c) adding a silicon source to the slurry; and d) shaping the slurry to form particles. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2009-207948 A [Patent Document 2] Special Publication No. 2008-537505 Summary of the Invention [Problem to be solved by the invention]

[0006] The present invention has an object to produce a zeolite molded body that is less susceptible to wear by using a method different from the methods described in the above-mentioned patent documents. [Means for solving the problem]

[0007] The present inventors have discovered that a zeolite molded body that is resistant to wear can be produced by using a polymeric crosslinking agent, rather than using only an inorganic binder as described in the above-mentioned patent documents, and have completed the present invention.

[0008] Specifically, a method for producing a zeolite molded body includes a slurrying step of preparing a slurry containing zeolite, an inorganic binder, and a polymeric crosslinking agent, and a molding step of spray-drying the slurry to mold a zeolite molded body, in which the content of the polymeric crosslinking agent in the slurry is in the range of 0.01 mass % to 10 mass % with respect to the total mass of the slurry excluding the polymeric crosslinking agent, and by using such a method, a zeolite molded body that is resistant to wear can be produced. Effect of the Invention

[0009] According to the present invention, a zeolite molded body that is resistant to wear can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The present invention includes an invention relating to a method for producing a zeolite shaped body that is resistant to wear (hereinafter, also referred to as the "production method of the present invention"). The production method of the present invention will be described in detail below. In the present invention, when a numerical range is indicated with "to", the numerical range includes the upper and lower limits. For example, when it is indicated with "1 to 2", it means "1 or more and 2 or less".

[0011] [Production method of the present invention] The manufacturing method of the present invention is characterized in that a slurry containing a polymeric crosslinking agent, zeolite, and an inorganic binder is prepared, and the slurry is spray-dried while the zeolite particles are crosslinked, thereby obtaining a zeolite molded body that is resistant to wear. Furthermore, this zeolite molded body is characterized in that it is resistant to wear even if the polymeric crosslinking agent is removed by firing. This is believed to be because the addition of the polymeric crosslinking agent suppresses the uneven distribution in the droplets due to the difference in mass transfer rate between the zeolite and the inorganic binder when the droplets are dried in the spray drying process, thereby making it possible to maintain the bond between the zeolite and the inorganic binder. The manufacturing method of the present invention will be described in detail below.

[0012] [Slurrying process] The manufacturing method of the present invention includes a slurrying step of preparing a slurry containing zeolite, an inorganic binder, and a polymeric crosslinking agent. In this step, the zeolite particles dispersed in the slurry are crosslinked with the polymeric crosslinking agent. This allows a zeolite molded body that is less susceptible to wear to be obtained by spray drying, which will be described later. Note that the slurry in the manufacturing method of the present invention refers to a suspension of liquid and solid particles.

[0013] In this step, a conventionally known zeolite can be used. The types of zeolite can be classified according to their crystal structure. Based on the code defined by the International Zeolite Society, zeolites having various crystal structures such as FAU, MFI, CHA, BEA, and MOR can be used. In the manufacturing method of the present invention, it is preferable to use either MFI or FAU, or both, which are effective as catalysts. Zeolites in which ion exchange or zeolite frameworks are partially substituted with alkali metals, alkaline earth metals, transition metals, typical metals, rare earth elements, and nonmetallic elements can also be used. The median diameter of the zeolite is preferably in the range of 0.1 μm to 10 μm, more preferably in the range of 0.5 μm to 8 μm, and particularly preferably in the range of 1 μm to 7 μm. When a zeolite having a median diameter in the above-mentioned range is used, a zeolite molded body that is less susceptible to wear is easily obtained. The median diameter is determined from the particle size distribution (volume basis) measured based on a laser diffraction / scattering method.

[0014] In this step, as the polymer crosslinking agent, a general polymer such as an ethylene-based resin, a cellulose-based resin, or a vinyl alcohol-based resin can be used. In this step, it is preferable to use at least one selected from methyl cellulose (MC), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyethylene oxide (PEO), and it is more preferable to use polyethylene oxide. When the above-mentioned compound is used as the polymer crosslinking agent, the zeolite particles can be crosslinked more strongly, so that a zeolite molded body that is less likely to be worn can be easily obtained. In addition, the average molecular weight of the polymer crosslinking agent is preferably in the range of 40,000 to 7,000,000, more preferably in the range of 50,000 to 6,000,000, and particularly preferably in the range of 60,000 to 4,000,000. When a polymer crosslinking agent having a molecular weight in the above-mentioned range is used, a zeolite molded body that is less likely to be worn can be easily obtained. The method of specifying the average molecular weight was performed using an HPLC Prominence504 system manufactured by Shimadzu Corporation. Specifically, the sample was dissolved in tetrahydrofuran (THF) to a concentration of about 0.1% by mass, and filtered through a hydrophilic PTFE filter having a pore size of 0.45 μm to remove insoluble matter, to prepare a measurement sample, which was then subjected to measurement.

[0015] In this step, a general compound can be used as the inorganic binder. In this step, at least one selected from silica, alumina, and clay minerals is preferred, and either or both of silica and alumina are more preferred, with silica being particularly preferred. Furthermore, the ratio (Wz:Wb) of the zeolite content (Wz) and the inorganic binder content (Wb) contained in the slurry is preferably in the range of 20:80 to 90:10, more preferably in the range of 25:75 to 85:15, and particularly preferably in the range of 30:70 to 80:20. When a slurry having this ratio in the above range is used, a zeolite molded body having a high zeolite content and low wear resistance is easily obtained.

[0016] In this step, a slurry is prepared by mixing zeolite, a polymer crosslinking agent, and a liquid (solvent). In this case, the liquid may be an organic solvent or water. Since the liquid is removed in the spray drying step described later, it is preferable to use water, which has a small environmental impact. If the zeolite aggregates in the liquid, it is recommended to disperse the zeolite using ultrasonic waves, a homogenizer, a colloid mill, or the like. By crosslinking the zeolite using a polymer crosslinking agent while the zeolite is dispersed in the liquid, a zeolite molded body that is less susceptible to wear can be obtained. In addition, the zeolite and the inorganic binder are mixed more uniformly.

[0017] In this step, the content of the polymer crosslinking agent in the slurry is in the range of 0.01% by mass to 10% by mass, preferably in the range of 0.05% by mass to 8% by mass, and more preferably in the range of 0.1% by mass to 5% by mass, based on the total mass of the slurry excluding the polymer crosslinking agent. By using a slurry in which the content of the polymer crosslinking agent falls within the above range, a zeolite molded body that is less susceptible to wear can be obtained. In the present invention, the content of the polymeric crosslinking agent in the slurry is an external ratio. That is, 100% by mass is calculated based on the total of all components (including zeolite, inorganic binder, and solvent) other than the polymeric crosslinking agent contained in the slurry, and the content of the polymeric crosslinking agent is expressed as a mass ratio to the total mass. Therefore, the above content of the polymeric crosslinking agent contained in the slurry being in the range of 0.01% by mass to 10% by mass with respect to the total mass of the slurry excluding the polymeric crosslinking agent is equivalent to the mass ratio of the total content of the components other than the polymeric crosslinking agent contained in the slurry to the content of the polymeric crosslinking agent contained in the slurry being in the range of 100:0.01-10. Therefore, the zeolite content (Wz), inorganic binder content (Wb), and solvent content in the present invention refer to values ​​calculated based on all components other than the polymer crosslinking agent contained in the slurry (as 100%). In this specification, "content" means "mass %" unless otherwise specified.

[0018] In this step, the sum of the content of zeolite (Wz) and the content of inorganic binder (Wb) contained in the slurry is in the range of 5% by mass to 50% by mass, preferably in the range of 15% by mass to 40% by mass, and more preferably in the range of 20% by mass to 35% by mass. By using a slurry in which the mass of the polymer crosslinking agent is in the above-mentioned range, a zeolite molded body that is less susceptible to wear can be obtained. The content of zeolite contained in the slurry is based on the mass of zeolite when the zeolite is fired at 1000°C for 1 hour.

[0019] In this step, the pH of the slurry is preferably in the range of 4 to 12, more preferably in the range of 5 to 10, and particularly preferably in the range of 6 to 9. When a slurry having a pH in the above-mentioned range is used, the dispersibility of the zeolite is increased, so that the zeolite is more easily crosslinked by the polymer crosslinking agent. In addition, the viscosity of the slurry is preferably in the range of 1 mPa·s to 5000 mPa·s, more preferably in the range of 5 mPa·s to 3000 mPa·s, and particularly preferably in the range of 10 mPa·s to 1000 mPa·s. When a slurry having a viscosity in the above-mentioned range is used, a spherical zeolite molded body is easily formed in the spray drying described below.

[0020] [Molding process] The production method of the present invention includes a forming step of spray-drying the slurry obtained in the above-mentioned step to form a zeolite molded body. Spray drying is a method in which the slurry is sprayed into a hot air current to remove the liquid in the sprayed slurry and mold the zeolite contained in the slurry into a spherical shape.

[0021] In this step, a conventionally known spray drying method can be used. The spray drying method includes a disk method in which a disk is used for spraying, and a nozzle method in which a nozzle is used for spraying. Either method may be used in this step. When the disk method is used, the size of the zeolite molded body obtained can be controlled by controlling the rotation speed of the disk. When the nozzle method is used, the size of the zeolite molded body obtained can be controlled by controlling the spray pressure and the nozzle diameter. In the spray drying, the inlet temperature of the hot air stream (the temperature of the hot air stream before the slurry is sprayed) is preferably lower than 500°C, and more preferably in the range of 100°C to 450°C. When the inlet temperature of the hot air stream is in the above-mentioned range, the crosslinking of the polymer crosslinking agent in the slurry is less likely to break, and a zeolite molded body that is less likely to wear can be obtained. In addition, the outlet temperature of the hot air stream (the temperature of the hot air stream after the slurry is sprayed) is preferably in the range of 50°C to 200°C, and more preferably in the range of 80°C to 150°C.

[0022] [Firing process] The manufacturing method of the present invention may include a calcination step of calcining the zeolite molded body obtained in the above-mentioned step. By calcining the zeolite molded body, the polymer crosslinking agent is removed. However, even if the polymer crosslinking agent is removed, the zeolite molded body after calcination is not easily worn. In addition, the manufacturing method may include a step of washing the zeolite molded body with ion-exchanged water or the like before or after the calcination step.

[0023] In this step, the zeolite molded body is preferably fired in a temperature range of 200 to 700°C, more preferably fired in a temperature range of 300 to 650°C, and particularly preferably fired in a temperature range of 350 to 600°C. Firing the zeolite molded body in the above-mentioned temperature range allows the polymer crosslinking agent to be removed efficiently. There is no particular restriction on the firing time, but firing is preferably performed in a range of 1 to 24 hours, more preferably in a range of 1 to 12 hours, and more preferably in a range of 1 to 6 hours.

[0024] The zeolite shaped body obtained by the manufacturing method of the present invention is preferably spherical. Whether the shape is spherical or not can be judged by directly observing the outer edge of the shaped body with the naked eye or a microscope. In this case, a total of 100 zeolite shaped bodies are observed, and if the outer edges of 90 or more of them correspond to a perfect circle or an irregular circle, it can be judged to be spherical. Here, an irregular circle refers to an ellipse in which the ratio of the minor axis to the major axis of the outer edge of the shaped body is 60% or more and less than 100%. In addition, the median diameter may be in the range of 1 μm to 1000 μm or less, 5 μm to 500 μm, or 10 μm to 100 μm. The median diameter can be specified by a measurement method described later. EXAMPLES

[0025] The production method of the present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0026] The measurement and evaluation methods used in the examples are as follows [1] to [4].

[0027] [1] Median diameter The median diameter was measured using a laser diffraction / scattering particle size distribution analyzer (LA-950V2) manufactured by Horiba, Ltd. Specifically, the sample was placed in a solvent (water) so that the light transmittance was in the range of 70-95%, and measurements were performed at a circulation rate of 2.8 L / min and 30 repetitions. The median diameter was calculated from the obtained particle size distribution (volume basis) using an attached analyzer.

[0028] [2] pH The pH was measured using a portable pH meter (D-51) manufactured by Horiba, Ltd. Specifically, an electrode calibrated with a standard solution was immersed 3 cm or more into the slurry, and the value displayed by the auto-hold measurement was used.

[0029] [3] Viscosity The viscosity was measured using a digital viscometer (TVB-10M) manufactured by Toki Sangyo Co., Ltd. Specifically, a rotor suitable for the viscosity of the slurry was used, and the value displayed at a rotation speed of 60 rpm and a measurement time of 30 seconds was used.

[0030] [4] Powdering rate The powdering rate was measured with reference to the JET-Cup method, which referred to ASTM (American Society for Testing and Materials)-5757-00. Specifically, the measurement object was baked at 500°C for 1 hour, and then 5g of water was added to 45g of the measurement object to adjust the humidity. Next, the measurement object was placed in an Atrrition device that was made by myself with reference to the above ASTM, and air (relative humidity of about 10%) was supplied at a rate of 7L / min by the Air JET method to flow the measurement object. At this time, the flow rate at the orifice outlet of the Atrrition device was 304m / s. For 5 to 20 hours after the start of flow, fine particles generated by abrasion were collected by a filter. The weight of the fine particles collected by the filter was divided by the weight of the measurement object that was placed to obtain the abrasion rate.

[0031] [Example 1] A slurry was prepared by mixing 250 g of zeolite (manufactured by JGC Catalysts and Chemicals: product name USY-5, FAU, median diameter 6 μm, ignition loss 1000 ° C-1 hour: 10%), 1.8 g of polymer crosslinker (manufactured by Meisei Chemicals: product name R-400, PEO, average molecular weight 200,000 to 300,000), 1.1 kg of inorganic binder (manufactured by JGC Catalysts and Chemicals: product name S-20L, silica, silica concentration 20.5%), and 250 g of ion-exchanged water. The constituents, content, pH, viscosity, etc. of the slurry are shown in Table 1.

[0032] The slurry obtained in the above-mentioned process was spray-dried using a spray dryer. The amount of hot air and the amount of slurry supplied were controlled so that the inlet temperature was 150°C and the outlet temperature was 90°C, and the zeolite molded body produced was collected. The zeolite molded body obtained was fired at 550°C for 3 hours using a muffle furnace. The shape of the fired zeolite molded body was observed using a microscope and found to be spherical. The median diameter of the zeolite molded body was measured using a laser diffraction / scattering particle size distribution measuring device and found to be 86 μm. Furthermore, the powdering rate was measured. The results are shown in Table 1.

[0033] [Example 2] Except for adjusting the content of the polymer crosslinking agent to 0.5% by mass, a zeolite shaped body was obtained in the same manner as in Example 1. Measurements and evaluations were also carried out in the same manner as in Example 1. The results are shown in Table 1.

[0034] [Example 3] Except for adjusting the content of the polymer crosslinking agent to 3 mass %, a zeolite shaped body was obtained in the same manner as in Example 1. Measurements and evaluations were also carried out in the same manner as in Example 1. The results are shown in Table 1.

[0035] [Example 4] Except for adjusting the content of the polymer crosslinking agent to 9 mass %, a zeolite shaped body was obtained in the same manner as in Example 1. Moreover, measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0036] [Example 5] A zeolite molded body was obtained in the same manner as in Example 2, except that the content ratio of the zeolite to the inorganic binder was adjusted to 70:30. Measurements and evaluations were also performed in the same manner as in Example 1. The results are shown in Table 1.

[0037] [Example 6] A zeolite molded body was obtained in the same manner as in Example 2, except that zeolite (manufactured by Süd-Chemie: product name ZSM-5 SAR80, MFI, median diameter 5 μm) was used. Measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.

[0038] [Comparative Example 1] Except for not using a polymeric cross-linking agent, a zeolite shaped body was obtained in the same manner as in Example 1. Measurements and evaluations were also carried out in the same manner as in Example 1. The results are shown in Table 1.

[0039] [Comparative Example 2] Except for adjusting the content of the polymer crosslinking agent to 12 mass %, a zeolite shaped body was obtained in the same manner as in Example 1. Moreover, measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0040] [Comparative Example 3] Except for not using a polymeric cross-linking agent, a zeolite shaped body was obtained in the same manner as in Example 6. Measurements and evaluations were carried out in the same manner as in Example 1. The results are shown in Table 1.

[0041] [Table 1]

Claims

1. a slurrying step of preparing a slurry containing zeolite, an inorganic binder and a polymeric crosslinking agent; A forming step of forming a zeolite molded body by spray drying the slurry, The content of the polymer crosslinking agent contained in the slurry is in the range of 0.01% by mass to 10% by mass with respect to the total mass of the slurry excluding the polymer crosslinking agent; A method for producing a shaped zeolite body.

2. The method for producing a shaped zeolite body according to claim 1, wherein the average molecular weight of the polymer crosslinking agent is in the range of 40,000 to 7,000,000.

3. The method for producing a zeolite molded body according to claim 2, wherein the polymer crosslinking agent is at least one selected from the group consisting of methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, and polyethylene oxide.

4. The method for producing a zeolite molded body according to claim 3, wherein a mass ratio (Wz:Wb) of a content (Wz) of the zeolite contained in the slurry to a content (Wb) of the inorganic binder contained in the slurry is in a range of 20:80 to 90:

10.

5. The method for producing a shaped zeolite body according to any one of claims 1 to 4, wherein the shaped zeolite body has a spherical shape and a diameter in the range of 1 µm to 1,000 µm.

Citation Information

Patent Citations

  • Catalysts, processes for their preparation and uses thereof

    JP2008537505A

  • Fluid catalytic cracking catalyst and its manufacturing method

    JP2009207948A